THE EFFECT OF USING AN EXTRA FAN ON CHANGES IN TEMPERATURE, VOLTAGE AND ELECTROLYTE SPECIFIC GRAVITY OF LEAD ACID BATTERIES IN ELECTRIC PALLET MOVERS - Sugianto, Rizaldy Adha (Universitas Mercu Buana, 2024)
Batteries are one of the vital components that are the main source of energy in electric forklifts which of course must be considered, especially their performance in issuing voltage and density of electrolyte which can be influenced by other factors such as temperature. The design of the battery itself tends to be closed so that it has very minimal air circulation which makes the hot temperature trapped and affects the performance of the battery itself. For these problems, an analysis of the addition of an extra fan on the battery cover was carried out to determine the extent of the extra fan's influence on battery performance (temperature, voltage, and electrolyte density) with a lead acid on the electric pallet mover. SPSS (Statistical Package for the Social Science) is used as a research method which is expected to produce data that shows how much influence the addition of an extra fan has on the battery performance of the electric pallet mover. The results of this study show that the addition of an extra fan to the pallet mover battery cover provides a significant change in the temperature, voltage, and density of the battery electrolyte. When the level of the extra fan is in the off state (none) compared to the level of the extra fan in the high speed state (6500 RPM) in the temperature test, the results show that the average change is 10.93oC. Then when the level of the extra fan is in the off state (none) compared to the level of the extra fan in the high speed state (6500 RPM) in the Voltage test, the results show that the average change is 0.6 volts. Meanwhile, when the extra fan level is in the off state (none) compared to the extra fan level in the high speed state (6500 RPM) in the Density test, the results show that the average change is 0.22.